The Includence and Clinical Significance of Cholelithiasis after Gastrectomy - Saito, Akira; Ishihara, Yukio; Noguchi, Takeo; Sonoda, Hitoshi; Mizuta, Tetsuaki; Karikomi, Kazuhiro (Nippon Shokaki Geka Gakkai zasshi, 1990)
We have studied the incidence and clinical significance of gallstones after gastrectomy in 110 patients with gastric cancer operated on between 1981 and 1986. A control group consisted of 33 patients with colo-rectal cancer operated on in the same period. Gallstones developed in 31% of all patients (34/110) during the 2. 5-year to 8. 5-year postgastrectomy follow-up and mostly within 4 years of gastrectomy. The majority of them were small and multiple and did not show an acoustic shadow on echograms of the gallbladder. Some of them dissolved spontaneously. The incidence of gallstones was 51% (20/39) after total gastrectomy, 20% (14/71) after subtotal gastrectomy and 9% (3/33) after resection of colo-rectal cancer. The incidence of gallstones was significantly higher after total gastrectomy than subtotal gastrectomy and colo-rectal resection. However, there was no statistical difference between subtotal gastrectomy and colo-rectal resection. Four patients developed symptoms and subsequently required biliary surgery. All of them received reconstruction by the Roux-Y technique after total gastrectomy. Cholelithiasis appears to be one of the major complications after total gastrectomy. It may be related mainly to the vagotomy performed at gastrectomy.